Human Platelet Gαq Deficiency Is Associated with Decreased Gαq Gene Expression in Platelets but not Neutrophils - Gabbeta, J.; Vaidyula, V. R.; Dhanasekaran, D. N.; Rao, A. K. (Thrombosis and Haemostasis, 2002)
G-proteins play an important role in platelet signal transduction and regulate responses upon activation of G-protein coupled receptors (GPCR). We have previously reported a patient with impaired platelet responses associated with deficiency in platelet Gαq. To understand the molecular basis for this defect, the cDNA sequence encoding Gαq (1080 bp) was obtained by reverse-transcription and polymerase chain reaction of platelet RNA; the cDNA sequence showed no mutations in the patient. Platelet Gαq mRNA levels were decreased by >50% compared to normal subjects; platelet Gαi2 mRNA levels were normal. Neutrophil calcium mobilization and elastase secretion, upon activation with several agonists, and neutrophil Gαq mRNA and protein levels were normal. These studies demonstrate that the patient has a defect in Gαq gene expression in platelets but not neutrophils, possibly due to defects in transcriptional regulation or mRNA stability, and suggest a hematopoietic-lineage specific defect.
Keywords: Platelet activation; Gαq; G-proteins; gene expression; signal transduction